Multilingual Processing Phenomena in Learners of Portuguese as a Third or Additional Language - Włosowicz, Teresa Maria (Theory and Practice of Second Language Acquisition, 2016)
The purpose of the study has been an analysis of Polish students’ cued translation of Polish (L1) and English or French (L2) sentences into Portuguese (third or additional language in De Angelis’s (2007) terminology). In particular, the study investigates cross-linguistic interaction (Herdina and Jessner’s (2002) term) in multilingual processing involved in L3 production. In fact, translation constitutes a special case of production because, on the one hand, the content is already contained in the L1 or L2 source sentences, but at the same time, this is not necessarily a facilitation, as the cues may require the use of words or structures the participants might not use in free production. The article is based on two studies carried out with thirty and forty-two students of Portuguese philology respectively. As the results show, cross-linguistic interaction in various directions was observed, not only from L2 (English or French), L3 (in those participants for whom Portuguese was an L4 and their L3 was Spanish or Italian), L4, etc. or, intralingually, from Portuguese, but also from L1, despite the distance between Polish and Portuguese and the special status of the native language. However, the amount of interference and/or negative transfer often depended on the sentence rather than on the language combination. The diversity of the observed interactions also supports Herdina and Jessner’s (2002) claim of the dynamic and unpredictable nature of cross-linguistic interaction.